2010
DOI: 10.1021/ml1000273
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Series of STAT3 Inhibitors by Virtual Screening

Abstract: The signal transducer and activator of transcription 3 (STAT3) is considered to be an attractive therapeutic target for oncology drug development. We identified a N-[2-(1,3,4-oxadiazolyl)]-4-quinolinecarboxamide derivative, STX-0119, as a novel STAT3 dimerization inhibitor by a virtual screen using a customized version of the DOCK4 program with the crystal structure of STAT3. In addition, we used in vitro cell-based assays such as the luciferase reporter gene assay and the fluorescence resonance energy transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 24 publications
1
100
0
Order By: Relevance
“…our study revealed that StX-0119 had a potent growth-inhibitory effect on the human lymphoma cell line Scc3 (Stat3-activated), and effectively down-regulated downstream target genes of the Stat3 signaling pathway including c-myc, Bcl-xL, cyclin D1 and survivin without significantly affecting Stat3 phosphorylation. Matsuno et al (15) reported similar results from experiments in vitro using human breast cancer MDa-MB-468 cells. More impressively, StX-0119 exhibited stronger growth inhibition against Scc3 tumors in vivo than did ag490.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…our study revealed that StX-0119 had a potent growth-inhibitory effect on the human lymphoma cell line Scc3 (Stat3-activated), and effectively down-regulated downstream target genes of the Stat3 signaling pathway including c-myc, Bcl-xL, cyclin D1 and survivin without significantly affecting Stat3 phosphorylation. Matsuno et al (15) reported similar results from experiments in vitro using human breast cancer MDa-MB-468 cells. More impressively, StX-0119 exhibited stronger growth inhibition against Scc3 tumors in vivo than did ag490.…”
Section: Discussionmentioning
confidence: 58%
“…considering the high concentration of StX-0119 in mouse plasma after an oral administration in a pharmacokinetic study reported previously (15), there may be a discrepancy between the plasma concentration and antitumor effect. Poor uptake of StX-0119 in the tumor site and a weak immunological antitumor effect in nude mice triggered by overcoming the Stat3-mediated immunosuppression induced in the tumor microenvironment (37) may be responsible for this discrepancy.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Recently, a series of novel STAT3 dimerization inhibitors was discovered through an SBVS campaign [213]. A database containing millions of compounds was filtered for drug-like properties, resulting in a final collection of approximately 360,000 molecules, which was then used in the SBVS.…”
Section: Identification Of a New Series Of Stat3 Inhibitors By Vsmentioning
confidence: 99%